2008
DOI: 10.1074/jbc.m800591200
|View full text |Cite
|
Sign up to set email alerts
|

A Histidine-rich and Cysteine-rich Metal-binding Domain at the C Terminus of Heat Shock Protein A from Helicobacter pylori

Abstract: HspA, a member of the GroES chaperonin family, is a small protein found in Helicobacter pylori with a unique histidineand cysteine-rich domain at the C terminus. In this work, we overexpressed, purified, and characterized this protein both in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
85
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 55 publications
2
85
0
3
Order By: Relevance
“…These include Hpn, an abundant histidine-rich protein (Gilbert et al, 1995;Ge et al, 2006), Hpn2 (Zeng et al, 2008), Mua (Benoit & Maier, 2008) and HspA, an unusual GroES homologue. HspA has a C-terminal extension containing a metal binding domain (Cun et al, 2008) that functions in nickel sequestration and detoxification, and in maturation of hydrogenase (Schauer et al, 2010). The Cterminal extension of HspA is only conserved in and restricted to H. pylori strains and the closely related Helicobacter acinonychis (Schauer et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These include Hpn, an abundant histidine-rich protein (Gilbert et al, 1995;Ge et al, 2006), Hpn2 (Zeng et al, 2008), Mua (Benoit & Maier, 2008) and HspA, an unusual GroES homologue. HspA has a C-terminal extension containing a metal binding domain (Cun et al, 2008) that functions in nickel sequestration and detoxification, and in maturation of hydrogenase (Schauer et al, 2010). The Cterminal extension of HspA is only conserved in and restricted to H. pylori strains and the closely related Helicobacter acinonychis (Schauer et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…13 Recently innovative metallomic and metalloproteomic approaches have aided identification of Bi targeting proteins in H. pylori such as HspA, Ef-Tu, NapA and urease (UreA and UreB) and revealed that Bi(III) has a high selectivity for cysteines and histidines, particularly motif patterns of CX n C, CX n H and HX n H. Evidence therefore suggests that Bi interference with metal homeostasis and oxidation reduction processes may be important. [14][15][16][17][18] Significantly it was recently demonstrated that glutathione and multidrug resistance protein transporter remove Bi from human cells, thereby protecting the human body from associated toxicity and also providing a level of selectivity between human cells and bacterial cells that lack glutathione such as H. pylori.…”
Section: Introductionmentioning
confidence: 99%
“…Domain B consists of 28 aa, including 8 histidine and 4 cysteine residues, with the latter forming two disulfide bonds, C94-C111 and C95-C112, generating a closed-loop structure (27). Apart from its cochaperone activity, HpGroES plays important roles in nickel homeostasis and urease activation (25,28,29). Besides these roles in intracellular locations (30), HpGroES is able to gain access to the extracellular compartment and is highly antigenic (29,31) and is specifically recognized by serum Abs in H. pylori-infected patients and is considered a potential candidate for vaccine development and diagnosis of H. pylori infection (32,33).…”
mentioning
confidence: 99%
“…In addition to the highly conserved GroES chaperonin domain, named domain A, HpGroES contains a C-terminal extension domain named domain B (residues 91-118), which is absent in the other GroES members (25). Domain B consists of 28 aa, including 8 histidine and 4 cysteine residues, with the latter forming two disulfide bonds, C94-C111 and C95-C112, generating a closed-loop structure (27).…”
mentioning
confidence: 99%
See 1 more Smart Citation